2018
DOI: 10.1002/prp2.440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiopulmonary bypass on the disposition of cefazolin in patients undergoing cardiothoracic surgery

Abstract: The aim of the study was to evaluate the disposition of plasma unbound cefazolin in patients undergoing cardiothoracic surgery with cardiopulmonary bypass (CPB). Adult patients undergoing cardiothoracic surgery with CPB were enrolled in the study. Cefazolin sodium was given intravenously before skin incision (1 g) and at the beginning of CPB (2 g). Thereafter, an additional dose (1 g) was given every 4 hours. Seven to ten blood samples were collected before and during surgery. Plasma total and unbound (ultrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…A low level of serum albumin is expected to result in a lower protein binding. Correlations between the albumin concentrations and protein binding were seen for cefazolin, ceftizoxime, ceftriaxone, and cefoperazone ( Ohashi et al, 1986 ; Fortunato et al, 1993 ; Allegaert et al, 2009 ; Himebauch et al, 2014 ; Schleibinger et al, 2015 ; de Cock et al, 2017 ; Asada et al, 2018 ; Kan et al, 2020 ; Booke et al, 2021 ; Hartman et al, 2021 ). However, the studies of Toth et al (1991) and Tsai et al (2016) showed no correlation between the albumin concentration and the protein binding of ceftriaxone.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…A low level of serum albumin is expected to result in a lower protein binding. Correlations between the albumin concentrations and protein binding were seen for cefazolin, ceftizoxime, ceftriaxone, and cefoperazone ( Ohashi et al, 1986 ; Fortunato et al, 1993 ; Allegaert et al, 2009 ; Himebauch et al, 2014 ; Schleibinger et al, 2015 ; de Cock et al, 2017 ; Asada et al, 2018 ; Kan et al, 2020 ; Booke et al, 2021 ; Hartman et al, 2021 ). However, the studies of Toth et al (1991) and Tsai et al (2016) showed no correlation between the albumin concentration and the protein binding of ceftriaxone.…”
Section: Resultsmentioning
confidence: 93%
“…Cardiopulmonary bypass (CPB) led to differences in protein binding during the procedure ( Hollis et al, 2015 ; de Cock et al, 2017 ; Asada et al, 2018 ). Cefazolin protein binding was shown to be low (53%–55%) during CBP ( Hollis et al, 2015 ; Asada et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the within‐day and between‐day variations (<15% at each concentration and <20% at the lowest concentration) were within the recommended guidelines (Table 1) of the US Food and Drug Administration, 2001). In addition, the preparation procedure for the 10‐fold dilution was simpler and faster than previous assays using blood samples (Asada et al, 2018). Moreover, the developed method determines the urinary cefazolin concentration within a short time (5 min), which is comparable with previously reported methods such as the HPLC–UV method (Kamani et al, 1998; Martinez et al, 1998).…”
Section: Discussionmentioning
confidence: 99%